Residual life of earthquake damaged structures. Issue 145 (June 2021) - Majhi, Deepti Ranjan; Shrikhande, Manish
Abstract: The problem of implied margin of safety in seismic design codes is examined — with particular reference to the Indian standard IS-1893. A framework for estimation of available margin of safety for earthquake resistant design is developed based on serviceability limit state using linear random vibration theory. Inadequacy of seismic zonation in ensuring the objective of uniform level of safety within each zone is shown with reference to differences in the available margins of safety for buildings designed for similar seismic zones but in distant geographical locations. Subsequently, the proposed reliability framework is extended to the problem of estimating residual life of earthquake damaged structures and also for developing a decision framework for planning of maintenance and repairs.